Asālīb Tadrīs Al-Imla’ Li Gair Al-Nāṭiqīna Bi Al-‘Arabiyyah - Ulum , Fatkhul (ALSINATUNA, 2018)
Imlā is in the high position among the branches of language. It constitutes an important foundation for written language. Errors in imlā can result in many problems and lead to errors in understanding sentence because of its unclear meaning. Students who are not Arabic speakers encounter many problems when learning this realm. Therefore, it is needed an appropriate method to adapt students language ability with their language level. This study aims to explain several methods of teaching Imla for non Arabic speakers. The suggested method here is adjusted with the four types of imlā, namely: Imlā Manqūl, Imla Manżūr, Imla Masmū’ and Imla Ikhtibāri. Besides it is provided with applicative examples in the teaching of imlā based on certain stages that should be taken by a teacher. Thus the teaching can be carried out pleasantly and satisfy all students needs in the lesson.This study uses the method of al-waşfi al-taḩlīli, a method that describes the problems that occur, by analyzing the causes and trying to find solutions to these problems.This research shows that the method of al-Nuşush al-Mutakāmilah is more effective and suitable for teaching imlā for non-Arab students, because it contains many positive things for teaching branches of Arabic.